Earthquake design practice for buildings - Booth, E. D. (Thomas Telford, 2006)
Talking about earthquake engineering, this second edition is intended for practising structural engineers, including those with little or no knowledge of the subject, and also for advanced engineering students. It discusses the provisions of seismic codes, particularly Eurocode 8.
Previous ed.: published as by David Key. 1988.
Keywords: Earthquake resistant design.; Buildings -- Earthquake effects.; elektronické knihy; electronic books